Total synthesis and stereochemical assignment of cryptolatifolione1. Issue 66 (19th July 2015) - Novaes, Luiz F. T.; Sarotti, Ariel M.; Pilli, Ronaldo A.
<x xml:space="preserve">Abstract</x> An enantioselective total synthesis of cryptolatifolione and its C-8 epimer is presented in a protecting-group-free fashion.